When prices hardly matter: Incomplete insurance contracts and markets for repair goods - Martin Nell; Andreas Richter; Jörg Schiller (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2006)
This paper looks at markets characterized by the fact that the demand side is insured. In these markets a consumer purchases a good to compensate consequen¬ces of unfavorable events, such as an accident or an illness. Insurance policies in most lines of insurance base indemnity on the insured's actual expenses, i.e., the insured would be partially or completely reimbursed when purchasing certain goods. In this setting we discuss the interaction between insurance and repair markets by focusing, on the one hand, upon the development of prices and the structure of markets with insured consumers, and, on the other hand, the resulting backlash on optimal insurance contracting. We show that even in the absence of ex post moral hazard the extension of insurance coverage will lead to an increase in prices as well as to a socially undesirable increase in the number of repair service suppliers, if repair markets are imperfect.
urn:nbn:de:bvb:19-epub-1187-3
Keywords: C72; D43; G22; 650; insurance; incomplete contracts; repair markets